2011
DOI: 10.1029/2010jb007964
|View full text |Cite
|
Sign up to set email alerts
|

Precursory seismic quiescence before theMw= 8.3 Tokachi-oki, Japan, earthquake on 26 September 2003 revealed by a re-examined earthquake catalog

Abstract: [1] The 2003 Tokachi-oki earthquake (M w = 8.3) occurred on 26 September 2003 off the pacific coast of Hokkaido, Japan. In the present study, an earthquake catalog is used that lists 2,000 earthquakes with M ≥ 3.3. All of the earthquake waveforms were recorded by the Institute of Seismology and Volcanology, Hokkaido University. In the present study, these waveforms are manually re-examined, and hypocenters and magnitudes are re-calculated. A detailed analysis of the re-determined earthquake catalog between 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 64 publications
1
10
1
1
Order By: Relevance
“…The quiescence area includes the epicenter of the main shock and overlaps with the asperity ruptured by the 2003 event. The seismic quiescence followed by the 2003 Tokachi-oki earthquake (M w 8.3) has been reported by Takahashi and Kasahara (2004) and Katsumata (2011a). The duration time of the seismic quiescence is found to be 9.8 years in this study, which is consistent with Takahashi and Kasahara (2004).…”
Section: Characteristic Of Seismic Quiescencesupporting
confidence: 91%
See 3 more Smart Citations
“…The quiescence area includes the epicenter of the main shock and overlaps with the asperity ruptured by the 2003 event. The seismic quiescence followed by the 2003 Tokachi-oki earthquake (M w 8.3) has been reported by Takahashi and Kasahara (2004) and Katsumata (2011a). The duration time of the seismic quiescence is found to be 9.8 years in this study, which is consistent with Takahashi and Kasahara (2004).…”
Section: Characteristic Of Seismic Quiescencesupporting
confidence: 91%
“…3:3 in a re-determined earthquake catalog between 1994 and 2003 and found that the duration time of the seismic quiescence was 5 years before the 2003 main shock. The earthquake catalog used by Katsumata (2011a) was too short to identify the long-term seismic quiescence during 9.8 years, thus it is not clear whether the results in Katsumata (2011a) are consistent with those in this study. Area the area numbers are the same as those shown in Fig.…”
Section: Characteristic Of Seismic Quiescencecontrasting
confidence: 57%
See 2 more Smart Citations
“…Some researchers find that there may be an acceleration period of seismic activity rather than the quiescence before some violent earthquakes (Bowman and King, 2001;Chen, 2003). However, with the development of seismic monitoring methods and the improvement of earthquake catalogue, more and more phenomena of quiescence before large earthquakes have been found (Wu and Chiao, 2006;Katsumata, 2011;Pu, 2018). The relationship between accelerating seismicity and quiescence is also highly regarded, as they are two major phenomena ahead of a main shock (Di Giovambattista and Tyupkin, 2004;Mignan and Di Giovambattista, 2008).…”
Section: The CV Fluctuates With the Increase Of Loadmentioning
confidence: 99%